Long-Term Impact of the COVID-19 Pandemic on In-Hospital Antibiotic Consumption and Antibiotic Resistance: A Time Series Analysis (2015-2021) - Marianna Meschiari; Lorenzo Onorato; Erica Bacca; Gabriella Orlando; Marianna Menozzi; Erica Franceschini; Andrea Bedini; Adriana Cervo; Antonella Santoro; Mario Sarti; Claudia Venturelli; Emanuela Biagioni; et al. (MDPI AG, 2022)
The coronavirus disease 2019 (COVID-19)-pandemic-related overload of health systems has compromised the application of antimicrobial stewardship (AS) models and infection prevention and control (IPC) programs. We aimed to evaluate the impact of COVID-19 on antimicrobial consumption (AC) and antimicrobial resistance (AMR) in the University Hospital of Modena. A time series analysis with an autoregressive integrated moving average model was conducted from January 2015 to October 2021 to evaluate the AC in the whole hospital and the intensive care unit (ICU), the incidence density (ID) of bloodstream infections (BSIs) due to the main multidrug-resistant organisms, and of C. difficile infections (CDIs). After an initial peak during the COVID-19 period, a decrease in the trend of AC was observed, both at the hospital (CT: −1.104, p = 0.025) and ICU levels (CT: −4.47, p = 0.047), with no significant difference in the single classes. Among the Gram-negative isolates, we observed a significant increase only in the level of BSIs due to carbapenem-susceptible Pseudomonas aeruginosa (CL: 1.477, 95% CI 0.130 to 2.824, p = 0.032). Considering Gram-positive bacteria, an increase in the level of BSIs due to methicillin-resistant Staphylococcus aureus and in the trend of CDIs were observed, though they did not reach statistical significance (CL: 0.72, 95% CI −0.039 to 1.48, p = 0.062; CT: 1.43, 95% CI −0.002 to 2.863, p = 0.051; respectively). Our findings demonstrated that the increases in AMR and AC that appeared in the first COVID-19 wave may be later controlled by restoring IPC and AS programs to pre-epidemic levels. A coordinated healthcare effort is necessary to address the longer-term impact of COVID-19 on AC to avoid irreversible consequences on AMR.